PENGEMBANGAN SISTEM INFORMASI ABSENSI KARYAWAN BERBASIS RFID 125 KHZ MENGGUNAKAN METODE AGILE DEVELOPMENT PADA PT. SANLY INDUSTRIES - Ucok Darmanto Soer; Sifa Fauziah; Iim Nursida (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The application of absences from work that occurred at PT. Sanly Industries, which has been happening during the pandemic, is still being carried out in each department by a staff. Absenteeism and overtime recording are still manual, and salary summaries are manual. The employee database is not provided with Microsoft Excel, which causes some problems that the system encounters in the company. In addition, handwritten absentee ballots are easily damaged, easily messed up, easily lost, easily damaged, and easily soiled. His RFID-Based Absence with RFID Reader is an alternative for Writers to overcome the problem of absence in the enterprise by using an interface Design using PHP and integrating with a MySQL database. We develop an absence information system using Agile Development methods. The development of this information system supports the processing of employee absences and is integrated with RFID cards that can be used as employee ID cards. The system speeds up the process of reimbursement of absences to help make the payroll process more effective and efficient, making issues related to the payroll process easier and more profitable.